A Systematic Review on Extreme Programming. Issue 1 (July 2021) - Shrivastava, Anchit; Jaggi, Isha; Katoch, Nandita; Gupta, Deepali; Gupta, Sheifali
Abstract: Since the advent of start-ups and old companies starting to shift to e-business, it has become troublesome to choose the right methods for projects that's where extreme programming came to use. In this paper, we tried to compile different applications of the same. Extreme programming is a well-known agile method for software development. Extreme programming ensures customer satisfaction, better software quality and efficient project management. The team size is usually small but the group is team-oriented. It is a dynamic software development model, i.e., continuous discussion and integration of new features and ideas is the cornerstone of this model.